Q: What is 4x2 plus x2?

Write your answer...

Submit

Related questions

Given 3x3 + 4x2 +x + 7 is divided by x2 + 1, find the results:

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

x3 + 4x2 + x + 4 = (x + 4)(x2 + 1)

4(x2 + 4)

2x(x2+2x+4)

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

It is an expression that can be simplified to: 4x2-42

4x2(x2-7x+10) 4x2(x-2)(x-5)

4x2 -x -1 :D

(x4 - 2x3 + 2x2 + x + 4) / (x2 + x + 1)You can work this out using long division:x2 - 3x + 4___________________________x2 + x + 1 ) x4 - 2x3 + 2x2 + x + 4x4 + x3 + x2-3x3 + x2 + x-3x3 - 3x2 - 3x4x2 + 4x + 44x2 + 4x + 40Râˆ´ x4 - 2x3 + 2x2 + x + 4 = (x2 + x + 1)(x2 - 3x + 4)

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

4x2 + 1 + x2 + 3 = 5x2 + 4

4(x2 - 6x + 13)

4x2 + 8x + 4 = 4 (x2 + 2x + 1) = 4 (x + 1)2

-4x2

9. And the word is minus, not minis.

x2 - (2x)2 = x2 - 4x2 = -3x2 x2 - 2x2 = -x2

If that's + 4x2, the answer is 2x(x2 + 2x - 4)

(12x2 + 18) / (3x2 + 6) = (4x2 + 6) / (x2 + 2)

4x2 + 8x + 4 = 4 (x2 + 2x + 1) = 4 (x + 1)2

5x2-2x+16=4x2+6x ,or x2-8x+16=0, or x2-2(x)(4)+(4)2=0, or (x-4)2=0, or (x-4)(x-4)=0, or x=4

Divide all terms by 4:- x2+7x+12 = (x+3)(x+4) when factored

Sure. It requires only the most basic algebraic manipulation of equalities.x2 + 6 = -4x2 + 2Add 4x2 to each side:5x2 + 6 = 2Subtract 2 from each side:5x2 + 4 = 0ax2 + bx + c = 0a = 5b = 0c = 4

4x2 plus 3=11

x2+8x = -3x2+5 4x2+8x-5 = 0 (2x+5)(2x-1) = 0 x = -5/2 or x = 1/2